Legal Awareness and Practical Approaches to Halalan Thayyiban Compliance: Insights from Street Food Vendors in Ponorogo, Indonesia - Rahmatika, Sania Dina; Bashori, Yudhi Achmad (Invest Journal of Sharia & Economic Law, 2024)
This study analyzes the understanding and implementation of the halalan thayyiban principle by street vendors in Ponorogo, Indonesia from a legal awareness perspective. Despite its importance in Islamic teaching, initial observations show that many vendors have not fully implemented this standard. Using an empirical law-based qualitative method, data were obtained through interviews, documentation, and observation and then analyzed inductively. The results revealed two categories of understanding: traders who understand halal in terms of substance, method of acquisition, and processing, and traders who equate thayyib with halal. Their strategies to maintain halalan thayyiban include maintaining cleanliness and using ingredients that are believed to be halal, but many have not met formal guidelines such as halal certification. Legal awareness is still low, although legal behaviors such as maintaining cleanliness have been implemented. This study highlights the need for government socialization and education to support traders in understanding and applying the principles of the halalan thayyiban. This research contributes to the development of halal policies in the informal sector and to understanding the role of legal awareness in micro businesses in Indonesia.